Réponses

2014-09-19T10:23:54+02:00
1) Le problème se traduit par :
x³=2x+1
(x+1)(x²-x-1)=x³-x²-x+x²-x-1=x³-2x-1
On a donc bien x³-2x-1=(x+1)(x²-x-1)

2) Si x>0 alors nécessairement x+1≠0
Or x³-2-1=0
⇔(x+1)(x²-x-1)=0
⇔x²-x-1=0 puisque x+1≠0

3) x²-x-1=x²-2*1/2*x+(1/2)²-(1/2)²-1
x²-x-1=(x-1/2)²-1/4-1=(x-1/2)²-5/4

x²-x-1=(x-1/2)²-5/4=(x-1/2+√5/2)(x-1/2-√5/2)
x²-x-1=(x-(1-√5)/2)(x-(1+√5)/2)

Donc x²-x-1=0
⇔(x-(1-√5)/2)(x-(1+√5)/2)=0
⇔x-(1-√5)/2=0 ou x-(1+√5)/2=0
⇔x=(1-√5)/2 ou x=(1+√5)/2
Or (1-√5)/2<0 donc la seule solution est x=(1+√5)/2